2017
DOI: 10.1007/s00268-017-4421-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intraoperative Nefopam Administration on Acute Postoperative Pain and Chronic Discomfort After Robotic or Endoscopic Assisted Thyroidectomy: A Randomized Clinical Trial

Abstract: We report that intravenous nefopam infusion during surgery decreased acute postoperative pain and the need for rescue analgesics, as well as chronic discomfort, following BABA robotic or endoscopic thyroidectomy without adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Fewer studies evaluated acetaminophen (two new; n = 290), 114,115 amantadine (two studies, one new; n = 82), 116,117 dexmedetomidine (one new; n = 80), 118 dextromethorphan (one study, not new; n = 50), 119 duloxetine (two new; n = 207), 120,121 etanercept (one new; n = 77), 122 fentanyl (one study, not new; n = 65), 123 magnesium (one new; n = 126), 94 memantine (one study, not new; n = 19), 124 mexiletine (two studies, not new; n = 175), 81,125 minocycline (two new; n = 231), 126,127 nefopam (four new; n = 307), 14,128–130 nitrous oxide (two studies, one new; n = 5,375), 131,132 valproic acid (one new; n = 128), 133 venlafaxine (one study, not new; n = 150), 78 and vitamin C (one new; n = 123). 134 Primary and secondary outcomes for drugs evaluated in fewer than five studies were inconclusive and shown in Supplemental Digital Content 12 (appendix L, http://links.lww.com/ALN/C639).…”
Section: Resultsmentioning
confidence: 99%
“…Fewer studies evaluated acetaminophen (two new; n = 290), 114,115 amantadine (two studies, one new; n = 82), 116,117 dexmedetomidine (one new; n = 80), 118 dextromethorphan (one study, not new; n = 50), 119 duloxetine (two new; n = 207), 120,121 etanercept (one new; n = 77), 122 fentanyl (one study, not new; n = 65), 123 magnesium (one new; n = 126), 94 memantine (one study, not new; n = 19), 124 mexiletine (two studies, not new; n = 175), 81,125 minocycline (two new; n = 231), 126,127 nefopam (four new; n = 307), 14,128–130 nitrous oxide (two studies, one new; n = 5,375), 131,132 valproic acid (one new; n = 128), 133 venlafaxine (one study, not new; n = 150), 78 and vitamin C (one new; n = 123). 134 Primary and secondary outcomes for drugs evaluated in fewer than five studies were inconclusive and shown in Supplemental Digital Content 12 (appendix L, http://links.lww.com/ALN/C639).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the MMA regimen controlled postoperative pain in the PACU and at 6, 12, and 24 h after thyroidectomy as effectively as fentanyl-based PCA. Postoperative pain after thyroidectomy is generally classified as mild-to-moderate surgical pain and is most intense within 6 h postoperatively [16]. There is a risk of providing opioid analgesics in excessive amounts or for a prolonged duration as PCA regimens cannot be sufficiently The systolic pressure immediately after intubation was lower in the MMA group than in the PCA group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the analgesic efficacy of nefopam in patients who underwent various types of robot-assisted surgeries. Patients who received nefopam during bilateral axillo-breast approach robotic or endoscopic thyroidectomy reported significantly lower postoperative pain scores and required fewer rescue analgesics compared to those receiving saline [ 27 , 28 , 29 ]. Similarly, in a study involving robotic nephrectomy, nefopam administration significantly reduced catheter-related bladder discomfort postoperatively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%